FOREIGN LANGUAGE ANXIETY AND ENGLISH ACHIVEMENT OF EIGHTH GRADE STUDENTS OF MTS SULAIMAN YASIN SAMARINDA IN THE 2011/2012 ACADEMIC YEAR - Ariani, Setya; Sunggingwati, Dyah; Iswari, Weningtyas Parama (CaLLs (Journal of Culture, Arts, Literature, and Linguistics), 2016)
Anxiety is considered having negative effects for most students in learning foreign language, especially English. It has attracted researchers’ attention to do the investigation on foreign language anxiety as a factor which inhibits students to learn the target language successfully. Concerning with this issue, this correlational research was emphasized on investigating the relationship between foreign language anxiety and students’ English achievement. Fifty-five eighth grade students of MTS Sulaiman Yasin Samarinda were asked to fill out 33 items of Foreign Language Classroom Anxiety Scale (FLCAS). The Pearson Product Moment Correlation showed that anxiety had significant negative correlation with students’ English achievement (r = -.258, p<.01). Key words: anxiety, achievement, Pearson Product Moment